Interpopulation hybridization generates meiotically stable rDNA epigenetic variants in allotetraploid Tragopogon mirus - Matyášek, Roman; Dobešová, Eva; Húska, Dalibor; Ježková, Ivana; Soltis, Pamela S; Soltis, Douglas E; Kovařík, Aleš (The Plant journal, 2016)
Uniparental silencing of 35S rRNA genes (rDNA), known as nucleolar dominance (ND), is common in interspecific hybrids. Allotetraploid Tragopogon mirus composed of Tragopogon dubius (d) and Tragopogon porrifolius (p) genomes shows highly variable ND. To examine the molecular basis of such variation, we studied the genetic and epigenetic features of rDNA homeologs in several lines derived from recently and independently formed natural populations. Inbred lines derived from T. mirus with a dominant d-rDNA homeolog transmitted this expression pattern over generations, which may explain why it is prevalent among natural populations. In contrast, lines derived from the p-rDNA dominant progenitor were meiotically unstable, frequently switching to co-dominance. Interpopulation crosses between progenitors displaying reciprocal ND resulted in d-rDNA dominance, indicating immediate suppression of p-homeologs in F1 hybrids. Original p-rDNA dominance was not restored in later generations, even in those segregants that inherited the corresponding parental rDNA genotype, thus indicating the generation of additional p-rDNA and d-rDNA epigenetic variants. Despite preserved intergenic spacer (IGS) structure, they showed altered cytosine methylation and chromatin condensation patterns, and a correlation between expression, hypomethylation of RNA Pol I promoters and chromatin decondensation was apparent. Reversion of such epigenetic variants occurred rarely, resulting in co-dominance maintained in individuals with distinct genotypes. Generally, interpopulation crosses may generate epialleles that are not present in natural populations, underlying epigenetic dynamics in young allopolyploids. We hypothesize that highly expressed variants with distinct IGS features may induce heritable epigenetic reprogramming of the partner rDNA arrays, harmonizing the expression of thousands of genes in allopolyploids.
Keywords: Gene Expression Regulation, Plant; chromatin modification; DNA, Plant; Polyploidy; nucleolar dominance; ribozomální DNA; epigenomika; Evolution, Molecular; fenotyp; epigenetic variants; umlčování genů; Tragopogon mirus; hybridizace genetická; ribosomal DNA; interpopulation hybridization; Phenotype; allopolyploid; Genotype; DNA rostlinná; regulace genové exprese u rostlin; DNA, Ribosomal; polyploidie; Gene Silencing; Hybridization, Genetic; genotyp; Epigenomics; genom rostlinný; Genome, Plant; DNA Methylation; metylace DNA; molekulární evoluce; Tragopogon